TRANSFORMASI NILAI RUKUN ISLAM DALAM PENINGKATAN SUMBER DAYA INSANI (SDI) BERPERADABAN - M.Samson Fajar (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
Islam as a true religion and universal. Islam is also a religion that includes rituals and spiritual values. The pillars of Islam must be understood as a value of ritual as well as spiritual, which must transform values into life, especially in the form of civilized human resources. The Tranformation process is carried out through a gradual process (tadarruj) of all the values embedded in its life. With this process, it will form a superior features of civilization Human resources with personal and social competencies Pillars of Islam as a strategy of forming superior quality of Human Resource, is making it as a gradual system in shaping of human Resource. The phasing begins with the formation of beliefs, character formation, financial formation, the formation of social sensitivity and the formation of internationally qualified individuals. Pillars of Islam as an Human Resource profile capable of global competitiveness should make it as a competency in building personal coopency and social and organizational competence. Personal competence includes the ability to build vision statements, change personality, and self-control in order to achieve success. While the social and organizational competence, including kemamapuan menysinergikan and potency in self and ummah to build strength, and ability to develop themselves continuously.